Winners and Losers: the Distributional Effects of the French Feebate on the Automobile Market. Issue 644 (21st October 2021) - Durrmeyer, Isis
Abstract: I quantify the welfare and environmental gains and losses from a policy establishing an environmental tax/subsidy for new cars in France in 2008. I estimate a structural model of demand and supply that features heterogeneity in consumer preferences to go beyond the average policy effects and analyse distributional aspects. The policy reduces average carbon emissions by 1.6% at the cost of additional emissions of local pollutants. The regulation favours middle-income individuals but has redistributive effects when combined with a tax that is proportional to income. Moreover, local pollutant emissions increase least in poor and rural areas, suggesting another redistribution channel.